A preliminary study investigating the neglected domain of mental health in Australian lifesavers and lifeguards - Samantha Fien; Jasmin C. Lawes; Jessica Ledger; Murray Drummond; Pamela Simon; Nancy Joseph; Shane Daw; Talitha Best; Robert Stanton; Ian de Terte (BMC, 2023)
Abstract Background Surf lifesavers and lifeguards have provided essential education, preventative, and rescue services to the Australian community for over 110 years. In this first responder role, surf lifesavers and lifeguards are inadvertently exposed to high risk and trauma related experiences, which may negatively impact mental well-being. To date however, there has been limited research into the mental health of surf lifesavers and lifeguards, and no studies at all on the mental health of adolescent surf lifesavers. The preliminary study aimed to measure the exposure of potentially traumatic events (PTEs), post-traumatic stress symptoms (PTSS), self-efficacy, social support, and attitudes towards mental health problems in Surf Life Saving (SLS) members. Methods An anonymous, online survey was developed (adolescent and adult versions) and created to measure the domain of mental health in surf lifesavers and lifeguards. Pearson's correlations investigated relationships between PTEs, PTSS, self-efficacy, social support, attitudes towards mental health problems, age, years as a SLS member, and years patrolling. Spearman's Rank was used for violations of normality. Results A total of 57 surf lifesavers/lifeguards aged 13-59 years were included in the final analysis. There was a significant positive relationship between exposure to direct trauma and PTSS, which in turn, were associated with greater negative attitudes towards mental health problems towards the mental health of others, and lower levels of self-efficacy. Male and female adults with PTSS reported lower social support, whereas for adolescent males, a positive relationship between direct trauma and PTSS was observed. Conclusion This research is the first to explore the mental health of Australian surf lifesavers and lifeguards. The results highlight the potential risks to mental health and well-being associated with this first responder role. More research to protect the vulnerability of this population is warranted.